The Ten Principles of Karaite Faith in a Seventeenth-Century Hebrew Poem from Troki - Tuori, Riikka (Acta Orientalia Vilnensia, 2017)
The ten principles of Karaite faith were originally compiled by medieval Byzantine Karaite scholars to sum up the basics of the Karaite Jewish creed. Early modern Karaites wrote poetic interpretations on the principles. This article provides an analysis and an English translation of a seventeenth-century Hebrew poem by the Lithuanian Karaite, Yehuda ben Aharon. In this didactic poem, Yehuda ben Aharon discusses the essence of divinity and the status of the People of Israel, the heavenly origin of the Torah, and future redemption. The popularity of Karaite commentaries and poems on the principles during the early modern period shows that dogma―and how to understand it correctly―had become central for the theological considerations of Karaite scholars. The source for this attentiveness is traced to the Byzantine Karaite literature written on the principles and to the treatment of the Maimonidean principles in late medieval rabbinic literature.